An experimental investigation on bearing behavior and failure mechanism of bolted composite interference-fit joints under thermal effects. (January 2022) - Hu, Junshan; Mi, Shiqing; Yang, Zhiyong; Wang, Changrui; Yang, Yuhang; Tian, Wei
Highlights: The residual effect of assembly parameters on behavior of composite joints were evaluated. Microscopy studies with X-ray technique were conducted to clarify thermal damage mechanism. The bearing response is slightly enhanced by low temperature and weakened by high temperature. The optimal benefit effect of assembly parameters changes with the variation of temperature. The localized damage area in composite joints propagates with the increase of temperature. Abstract: This paper reports an experimental investigation on bearing behavior and failure mechanism of single-lap bolted composite interference-fit joints under thermal effects. To achieve this target, testing temperatures ranged from −25 to 110 ℃ were designed to simulate thermal service environments. The unidirectional composite lamina was tested longitudinally and transversely to figure out potential change of material properties induced by thermal loading. The residual effects of stacking sequence, interference-fit size and tightening torque on bearing strength and stiffness of composite joints after exposed to thermal conditions were evaluated. Microscopic studies applying X-ray technique on damage areas to monitor damage evolution were conducted to comprehend the thermal failure mechanism. The results evidence that the bearing performance of composite joints was slightly enhanced by low temperature due to cold hardening of matrix resin but greatly weakened by high temperature owing to the combined effects of heat softening of resin, residual stress relaxation and thermal expansion of joint components. Tightening torque to enhance bearing performance is the most beneficial at room temperature, whereas the interference-fit remains the dominant influence at sub-freezing environments. In conclusion, thermal loading plays an important role in bolted composite interference-fit joints. It is an unneglectable factor that would enlarge damage area, alter failure mode and should be understood thoroughly.